Programming and implementation for a camera-based linear guide tracking system for a landing platform (control) - Lim, Yan Yu (Nanyang Technological University, 2020)
This paper reflects the learning journey and the step-by-step guide of the student attempting to produce autonomous landing functions for the widely increasing popular quadrotor drone. Autonomous landing function for drones attracted many institutions and organizations in the research and development over the years. This function opens a wider range of capabilities in areas such as surveillance and goods delivery, etc. It is indeed a giant leap towards an autonomous future with high-tech services and massive use of artificial intelligence. Hence, this paper will discuss the trends and uses of autonomous drones, the fundamental theories, as well as the implementations by the student. As the autonomous drone’s function covers a wide range of topics such as physical controls, cameras intelligence, battery swapping functions, etc., the student will mainly focus on the control area of the autonomous landing function for his final-year-project.